2009
DOI: 10.1073/pnas.0813368106
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal lymphangiogenesis in idiopathic pulmonary fibrosis with insights into cellular and molecular mechanisms

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, debilitating respiratory disease whose pathogenesis is poorly understood. In IPF, the lung parenchyma undergoes extensive remodeling. We hypothesized that lymphangiogenesis is part of lung remodeling and sought to characterize pathways leading to lymphangiogenesis in IPF. We found that the diameter of lymphatic vessels in alveolar spaces in IPF lung tissue correlated with disease severity, suggesting that the alveolar microenvironment plays a role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 43 publications
9
93
1
Order By: Relevance
“…19 This study adds to the information previously described by El-Chemaly et al, 10 who reported that the area of LVs inversely correlate with disease severity in UIP. Our study included normal-tissue stereologic assessments, as well as samples from the most common forms of IIP, UIP, and NSIP.…”
Section: Quantifi Cation Of Serum Levels Of Vascular Endothelial Growsupporting
confidence: 70%
See 2 more Smart Citations
“…19 This study adds to the information previously described by El-Chemaly et al, 10 who reported that the area of LVs inversely correlate with disease severity in UIP. Our study included normal-tissue stereologic assessments, as well as samples from the most common forms of IIP, UIP, and NSIP.…”
Section: Quantifi Cation Of Serum Levels Of Vascular Endothelial Growsupporting
confidence: 70%
“…Furthermore, the patients with UIP or NSIP in the present study were fully characterized clinically using pulmonary function testing and chest CT scans. LV volume density was also increased in patients with UIP compared with the normal control group, in keeping with the fi ndings presented by El-Chemaly et al 10 In our study, LV volume density, although increased in both UIP and NSIP, was not associated with any metrics of parenchymal component volume density or any metrics of clinical severity, whereas the El-Chemaly et al 10 study found a negative association between LV area and disease severity in UIP. One explanation for the discrepancy is that the samples used in the present study were less subject to sampling and orientation bias and were are not limited by the usual pitfalls of randomization and lack of data pertaining to vessel length.…”
Section: Quantifi Cation Of Serum Levels Of Vascular Endothelial Growsupporting
confidence: 67%
See 1 more Smart Citation
“…It is well known that mediastinal lymphadenopathy is present in a significant amount of patients with IPF [104,105]. In the study of EL-CHEMALY et al [106], lymphatic vessels in IPF lungs were in close proximity to alveolar spaces, even in those areas with a well-preserved architecture. Moreover lymphatic vessels were present throughout the fibrotic tissue and in close proximity to the main bronchovascular tree.…”
Section: Lymphatics and Pulmonary Fibrosismentioning
confidence: 96%
“…Finally, in human idiopathic pulmonary fibrosis, alveolar lymphangiogenesis correlates with the disease severity. CD11b þ macrophages from bronchoalveolar lavage fluid from pulmonary fibrosis patients, but not from healthy subjects, are able to form tube like structures in vitro expressing the LEC markers LYVE-1 and podoplanin (El-Chemaly et al 2009). These results indicate that inflammation is a prerequisite for the potential transdifferentiation of myeloid cells into LECs.…”
Section: Myeloid-endothelial Plasticity In Pathological Inflammation mentioning
confidence: 99%